Vrstovni sastav Marulićeve hrvatske lirike - Fališevac, Dunja (Array, 2001)
The following lyrical models are described and set apart as the dominant types in Marulić's work:1)the lyric appeal and 2) the lyric portrayal, with the subtypes od a) the lyric narrative and b) the lyric dialogue.